Perancangan Aplikasi E-Commerce Untuk UKM - Nyoman Ayu Nila Dewi (Media Aplikom, 2017)
Small and Medium Enterprises (SMEs) form the Reviews largest group of economic actors in the Indonesian economy. Product marketing for SMEs is a factor that can make-an SME to develop. Traditional way in product marketing is Carried out by SMEs and this is one of the factors inhibiting the development of SMEs to face competition that is globally competitive. To help expand the market and gain the flexibility to trade, SMEs should use information technology that is used as a medium of global business communications. By utilizing e -commerce in its business operations, SMEs will gain access to a wider market and Potentially new customers. On the other hand, customers will more Easily Obtain The Necessary information on-line. Information system that can be a forum for SMEs to market Reviews their products without having to create or develop an information system e-commerce itself. Keywords:e-commerce, SMB, System Design